A family of linear stable equilibria in the Sun-Earth-Sail problem - Marchesin, Marcelo; Yokoyama, Tadashi [UNESP] (Springer Nature, 2020)
The collinear libration point of the Sun-Earth Circular Restricted Three-Body Problem (CR3BP), L3 is located opposite to the Earth with respect to the Sun. Whereas several space missions have been launched to the other two collinear equilibrium points, i.e., L1 and L2, the region around L3 is so far unexploited essentially because of the severe communication limitations caused by Sun’s blocking location. By using an adequate size, location and attitude of a solar sail, the equilibrium point can be displaced from its original location to allow direct communication between the satellite and Earth. This paper presents several families of artificial equilibria located on the semi-space which is permanently opposite to Earth in relation to the Sun, but which allows direct communication with Earth. We present a family of such equilibria which are linearly stable and therefore very useful for space missions.
Keywords: Artificial equilibria; Linear stability; Sail dynamics